2014
DOI: 10.4236/aim.2014.416134
|View full text |Cite
|
Sign up to set email alerts
|

Enrichment of <i>Artemia</i> (Leach) nauplii with Canola Oil: Effect on <i>Heros severus</i> (Heckel) Larvae Performance and Environmental Stress

Abstract: The effect of canola oil enriched Artemia (Leach) nauplii on growth, survival, resistance to environmental stresses of temperature and oxygen deficiency and fatty acid composition in severum fish, Heros severus (Heckel), larvae were investigated. The larvae (average weight 3 mg ± 0.83) were fed 4 times daily starting at the onset of exogenous feeding for 18 days. Triplicate groups of fish were offered one of two treatments: 1) newly hatched Artemia (Leach) nauplii (unenriched) and 2) canola oil enriched Artemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
(27 reference statements)
1
1
0
Order By: Relevance
“…The study reported that the POME significantly enhanced the rotifer production, and improved growth and survival. Concordant findings were also obtained on other plant oil-based enriched live foods for different species (Smith et al, 2004;Menoyo et al, 2007;Huanng et al, 2008;Hafezieh et al, 2010;Tehrani et al, 2014;Kazemi et al, 2016). The morphological features (phenotypic characters), CF and TL/W ratio that are normally used as indicators of nutritional status of fish larvae showed that the Asian seabass larvae were developing normally based on the consistent pattern in all the treatment groups.…”
Section: Discussionsupporting
confidence: 53%
“…The study reported that the POME significantly enhanced the rotifer production, and improved growth and survival. Concordant findings were also obtained on other plant oil-based enriched live foods for different species (Smith et al, 2004;Menoyo et al, 2007;Huanng et al, 2008;Hafezieh et al, 2010;Tehrani et al, 2014;Kazemi et al, 2016). The morphological features (phenotypic characters), CF and TL/W ratio that are normally used as indicators of nutritional status of fish larvae showed that the Asian seabass larvae were developing normally based on the consistent pattern in all the treatment groups.…”
Section: Discussionsupporting
confidence: 53%
“…This includes diseases associated with aquatic organisms (Whittington and Chong, 2007;Lawson et al, 2015), invasive species release (Padilla and Williams, 2004;Delaney et al, 2008;Howeth et al, 2016;Bandaranayake and Chandrasekara, 2017;Magalhães et al, 2017;Selwyn et al, 2017;Tuckett et al, 2017) and use for popular aquarium species for breeding and scientific research (Hoff, 1996;Moe, 2003;Moorhead and Zeng, 2010;Olivotto et al, 2011;Domínguez and Botella, 2014;Tehrani et al, 2014). Another, far less common focus for research includes the human dimensions of the aquarium trade and hobby.…”
Section: Introduction To Home Aquarium Keepingmentioning
confidence: 99%